The Correlation between Serum Vitamin D and Total IgE Levels and Chronic Spontaneous Urticaria among Chinese Population: A Retrospective Study - Jia Liu; Fudong Wang; Hui Cao; Yulan Wang; Furong Liang; Shuling Jiang; Haofeng Zhang; Jingying Luo (Indian Journal of Dermatology)
Objective: This study aims to investigate the relationship between serum vitamin D, total IgE levels and chronic spontaneous urticaria (CSU). Methods: We collected data from 101 patients with chronic spontaneous urticaria (experimental group) and 115 healthy normal subjects (control group) in the same period of physical examination. Results: The results showed that the number of deficient and absolute deficient 25-hydroxyvitamin D in the experimental group was significantly lower than in the control group (P < 0.05). Pearson correlation analysis showed that the activity score of CSU patients was negatively correlated with serum vitamin D (r = −0.2278, P = 0.0220) and positively correlated with IgE (r = 0.2078, P = 0.0380). It was observed that serum vitamin D in CSU patients was negatively correlated with their activity (r = −0.2278, P = 0.0220) and positively correlated with age (r = 0.2675, P = 0.0069). The Point-biserial correlation analysis revealed that gender was positively correlated with serum vitamin D (Pearson correlation coefficient = 0.286, P = 0.004) and UAS score (Pearson correlation coefficient = 0.273, P = 0.006). Ordinal logistic regression analysis showed that only serum vitamin D was correlated to activity scores (P = 0.008). In addition to activity scores, age (P = 0.005) and gender (P = 0.04) were correlated to serum vitamin D. Conclusion: The activity score of CSU patients was negatively correlated with serum vitamin D and positively correlated with IgE. Serum vitamin D in CSU patients was negatively correlated with activity score and disease duration and positively correlated with age and gender.